Tenure security, landscape governance, and climate change: A research agenda - McCarthy, Nancy (International Food Policy Research Institute, 2021)
The impacts of climate change are already occurring across the globe, from droughts to floods, damagingly high temperatures, and sea-level rise. Many smallholder farmers were already vulnerable to weather extremes, and in the absence of effective adaptation measures, this vulnerability will only increase over time. While certain weather patterns associated with climate change are happening even now, future changes remain uncertain. Policy-relevant research needs to assess the benefits of flexible responses to future climate changes, while recognizing the costs of flexibility.